2020
DOI: 10.3389/feart.2020.563453
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostratigraphic Chronology of a Cenozoic Sequence From DSDP Site 274, Ross Sea, Antarctica

Abstract: New paleomagnetic results from the late Eocene-Middle Miocene samples from Deep Sea Drilling Project Site 274, cored during Leg 28 on the continental rise off Victoria Land, Ross Sea, provide a chronostratigraphic framework for an existing paleoclimate archive during a key period of Antarctic climate and ice sheet evolution. Based on this new age model, the cored late Eocene-Middle Miocene sequence covers an interval of almost 20 Myr (from ∼35 to ∼15 Ma). Biostratigraphic constraints allow a number of possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 97 publications
(107 reference statements)
3
7
0
Order By: Relevance
“…e lower part, cores 35-43, has a very low recovery and is prone to normal polarity directions. Magnetostratigraphic results for the upper Oligocene generally agree with those recently published by Jovane et al (2020), as shown in Figure 2. For the lower part of the record, our biostratigraphic results provide new tie points that indicate a lower-Oligocene age, instead of the previously published upper-Eocene age (Hayes et al, 1975;Jovane et al, 2020).…”
Section: Reworked Versus In Situ Dinocystssupporting
confidence: 90%
See 2 more Smart Citations
“…e lower part, cores 35-43, has a very low recovery and is prone to normal polarity directions. Magnetostratigraphic results for the upper Oligocene generally agree with those recently published by Jovane et al (2020), as shown in Figure 2. For the lower part of the record, our biostratigraphic results provide new tie points that indicate a lower-Oligocene age, instead of the previously published upper-Eocene age (Hayes et al, 1975;Jovane et al, 2020).…”
Section: Reworked Versus In Situ Dinocystssupporting
confidence: 90%
“…Magnetostratigraphic results for the upper Oligocene generally agree with those recently published by Jovane et al (2020), as shown in Figure 2. For the lower part of the record, our biostratigraphic results provide new tie points that indicate a lower-Oligocene age, instead of the previously published upper-Eocene age (Hayes et al, 1975;Jovane et al, 2020). e presence of the marker dinocyst Malvinia escutiana (FO = 33.7 Ma; Houben et al, 2011Houben et al, , 2019 in the lowermost sediment sample (Core 43, 404.66 mbsf), directly overlying the basement, indicates an Early-Oligocene age of the lowermost sediment that was also suggested from the age of the underlying ocean crust (Cande et al, 2000).…”
Section: Reworked Versus In Situ Dinocystssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the Miocene was a significant time for phosphogenesis globally. Important global phosphogenesis events coincided with two significant global climatic shifts: (a) during the Eocene-Oligocene boundary (∼34 Ma), when climate shifted from a warmer to a glacial Earth and (b) the late Oligocene-early Miocene transition (∼27-21 Ma) during a shift from a glacial to warmer Earth (Hein et al, 1993;Hyeong et al, 2013;Jovane et al, 2020;Schöllhorn et al, 2019). According to Sheldon (1980), major climatic shifts initiated phosphogenesis in the oceans because they promoted intense oceanic vertical mixing that mobilized high amounts of phosphorus stored in the deep ocean after long periods of sluggish vertical mixing.…”
Section: Phosphatization and Past Oceanographic Conditions At Rio Grande Risementioning
confidence: 99%
“…The abbreviations of the dinocysts species can be found in Table 1. The data were plotted in the C2 software program (Juggins, 2007). The analysis scores are provided in Table S4.…”
Section: Correspondence Analysismentioning
confidence: 99%